The role and capability of Imami educational systems in Islamic culture and civilization progress (considering the first five centuries) - Mohammad javad yavari Sarsakhti; esmaeil kazemi zorami (Pizhūhish/hā-yi rahbarī va mudīriyyat-i āmūzishī, 2018)
Among all aspects of cultural and civilization activities, teaching science and politeness has been one of the most interesting topics. Today, this topic also likes one of the main sign of development for societies and countries. It is clear that educational system has an important role and also motivator of designing culture and civilization as one part of Islamic civilization structure. But, considering some critics about disability of Imami educational systems and their achievements at the first five centuries, their performance not only should be admired, but also its role must be considered and studied as one of the main influential existence. So, this research deals with this topic and considers both the critics and capabilities of this educational system. Considering the goal of establishing the Imami educational system, it is found that the system, for the sake of having some components which have abilities to design and make capacities, has an important role to design and progress the Islamic culture and civilization. Shia’ by utilizing their advance thoughts, they could design and generate science and politeness and has important role in both the educational systems, and culture and civilization progress.